The Late Third Millennium BCE in the Upper Orontes Valley, Syria : ceramics, chronology and cultural connections - Kennedy, Melissa, 1984- (Ancient Near Eastern studies. Supplement, 2015)
This volume is a revised version of a doctoral dissertation undertaken at The University of Sydney. It examines the florescene of urban society during the mid to late Third Millennium BCE in the northern Levant, focusing on the largely unexplored region of the upper Orontes Valley, specifically the site of Tell Nebi Mend, ancient Qadesh (on the Orontes). This work seeks to explore the role and significance of 'small' regional sites during the Early Bronze Age IV, by presenting a detailed stratigraphic and ceramic analysis of the Tell Nebi Mend sequence from the mid Third Millennium (Early Bronze Age III) through the early Second Millennium BCE (Middle Bronze Age I). One of the principal aims of this work is to construct a detailed ceramic typology for Tell Nebi Mend and the upper Orontes during the late Third Millennium BCE. This stratigraphically anchored assemblage was designed as a foil for the more intensively investigated 'mega-site' sequences of the region, such as Ebla and Hama. It was also designed to explore and examine the development and evolution of regional ceramic horizons and the growth of inter-site interaction that occurred during the later Early Bronze Age. Although this work will not be the last word on studies of the EB IV, the ceramic and stratigraphic information presented sheds a new and important light on many of the key research issues that surround the Early Bronze Age IV, such as the nature of the Early Bronze Age III-IV transition and the regional response to the 'collapse' of the Early Bronze Age urban system ca. 2000 BCE.